2010
DOI: 10.3109/01443615.2010.501412
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer in Indian rural women: Trends over two decades

Abstract: Worldwide, cervical cancer is considered to be the second commonest cancer as far as mortality and incidence is concerned and India contributes to about 20–30% of the global burden. This paper is based on analysis of records of persons suffering from various cancers over 25 years. Cervical cancer constituted 14.4% of all cancers of men and women put together, 28.8% of the cancers in women and 73.3% of all gynaecological cancer. The cases studied were divided into five Blocks: Block A 1983–1987; Block B 1988–19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…18 Chhabra et al found an increase in cervical cancer among outpatients from 0.55% in 1983 to 3.5% in 2007. 19 But over the years from 1983-1987 to 2003-2007 there was a fall in the percentage of all cervical cancers from 43.8% to 37.6%. On the other hand, in Odisha, cancer cervix was the second most common cancer, with an increase of 3.1% from 2001 to 2011.…”
Section: Resultsmentioning
confidence: 99%
“…18 Chhabra et al found an increase in cervical cancer among outpatients from 0.55% in 1983 to 3.5% in 2007. 19 But over the years from 1983-1987 to 2003-2007 there was a fall in the percentage of all cervical cancers from 43.8% to 37.6%. On the other hand, in Odisha, cancer cervix was the second most common cancer, with an increase of 3.1% from 2001 to 2011.…”
Section: Resultsmentioning
confidence: 99%
“…Of all cases of cervical cancer in the world, 85% occur in developing countries, and of all the deaths which occur due to cervical cancer in the world 88% are in developing countries [5][6][7]. In one of our earlier studies, cervical cancer constituted 29% of all cancers in women and others also report similar figures [8]. Cervical cancer is the second most frequent cause of cancer deaths in women [9].…”
Section: Introductionmentioning
confidence: 94%
“…Cervical cancer is rampant here but not vaginal. Our earlier study had revealed that 73.3% of all gynecological cancer cases were cervical with an increase in cervical cancer cases, over the years [13], but only 30 cases of primary vaginal cancer were diagnosed in 3 decades. Dhakal [14] has reported 2.7% vaginal cancer and 85.23% cervical amongst all gynecological cancers.…”
Section: Journal Of Universal Surgery Issn 2254-6758mentioning
confidence: 99%